Participation to the first Cybathlon: an overview of the FREEWHEELS team FES-cycling solution - Benoît Sijobert; Charles Fattal; Anne Daubigney; Christine Azevedo-Coste (European Journal of Translational Myology, 2017)
This article is a contribution to a special issue aiming at collecting data and documenting the different specificities of the teams which participated into Cybathlon 2016 FES-bike discipline. Our team prepared one paraplegic pilot over one year and developed a FES-cycling device based on existing commercial products. Our pilot (47 y.o, spinal cord lesion T3 AIS A since year 1995) was qualified for the final race and finished in 6th position over 12 participants in the discipline, covering a total distance of 750m at an average speed of 5.71km/h, propelled by his own quadriceps and hamstrings muscles.